2010
DOI: 10.3109/08860220903367502
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Patients with End Stage Renal Disease Admitted to an Intensive Care Unit in India

Abstract: Outcome of ESRD patients admitted to ICU is poor, especially if they require other organ support. APACHE II and SOFA scores perform well as predictors of 30-day mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 17 publications
3
28
3
Order By: Relevance
“…4 Devan juneja et al, study during 2010 on outcome of patients with end stage renal disease admitted to an intensive care unit, 73 patient they observed and mean APACHE II score were 26 (14-49), SOFA score were 7(4-17). 8 In M P Halle et al, study mean sofa score in survivors were 6 and non survivors were 8.In present study mean sofa score were 8.8 ± 2.5.…”
Section: Severity Of Acute Pulmonary Edemasupporting
confidence: 46%
“…4 Devan juneja et al, study during 2010 on outcome of patients with end stage renal disease admitted to an intensive care unit, 73 patient they observed and mean APACHE II score were 26 (14-49), SOFA score were 7(4-17). 8 In M P Halle et al, study mean sofa score in survivors were 6 and non survivors were 8.In present study mean sofa score were 8.8 ± 2.5.…”
Section: Severity Of Acute Pulmonary Edemasupporting
confidence: 46%
“…As expected, physiological, and biochemical disturbances including hypotension, bradycardia, tachypnoea, hypoxia, reduced Glasgow Coma Score, hyponatraemia, leucopenia, and sepsis within the first 24 hours of ICU admission exert a significant impact on hospital mortality, too [4]. Mechanical ventilation and the need for inotropic support are also significantly associated with mortality at 30 days [13]. Whilst many of these variables are risk factors for mortality in ICU patients in general, their impact on the ESRD population appears to be greater, perhaps due to a lack of physiological reserve in this group.…”
Section: Longer-term Outcomesmentioning
confidence: 92%
“…Gastrointestinal bleeding is the third most common reason for chronic dialysis patients to require critical care, with studies estimating rates of 2.7% to 20% in critically unwell dialysis patients [7, 10, 13, 14]. …”
Section: Characteristics Of Critically Ill Dialysis Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dialysis patients are more likely to be admitted to the ICU for medical rather than surgical conditions [2,3]. The most frequent admission diagnoses for dialysis patients are related to sepsis and cardiovascular disease [3,4,8,9,10]. Interestingly, a number of studies have reported a higher rate of cardiac arrest prior to ICU admission in dialysis patients [11,12,13,14].…”
Section: Epidemiology Of Critical Illness In Dialysis Patientsmentioning
confidence: 99%